Blood pressure reduction in higher cardiovascular risk patients in the Global SYMPLICITY Registry. (3rd October 2022) - Rodriguez, O; Mahfoud, F; Schmieder, R; Schlaich, M; Narkiewicz, K; Ruilope, L; Williams, B; Fahy, M; Mancia, G; Boehm, M
Abstract: Background/Introduction: The Global SYMPLICITY Registry (GSR) was designed to evaluate the safety and efficacy of renal denervation (RDN) in real-world patients. Inclusion and exclusion criteria are limited to allow assessment of the effects of RDN on patients with a wide range of comorbidities. The current analysis examines blood pressure (BP) reduction after RDN in higher cardiovascular risk patients. Purpose: To evaluate blood pressure reduction after RDN in higher cardiovascular risk patients in GSR. Methods: GSR is a prospective all-comers registry to evaluate the safety and efficacy of RDN. Patients are enrolled in GSR and receive radiofrequency RDN using the Symplicity Flex or Symplicity Spyral catheter. Office and ambulatory BP are measured at each follow-up (3, 6, 12, 24, and 36 months). In this post-hoc analysis, changes from baseline in office and 24-hour ambulatory systolic blood pressure were assessed in patients at higher cardiovascular risk. Higher risk was defined using baseline office systolic or diastolic BP as well as additional risk factors (Figure 1). Results: As of March 2021, there were 2621 patients characterized as higher cardiovascular risk in GSR. Baseline characteristics included mean age 60.7±12.1 years, 57.6% male, 37.9% type 2 diabetes, 35.8% hypocholesterolemia, 19.7% eGFR <60 mL/min/1.73 m 2, 16.2% left ventricular hypertrophy, 10.2% previous stroke and 9.3% previous myocardial infarction. Baseline office systolic BP (OSBP) was 168.8±22.7 mmHg and baseline ambulatory systolic BP (ASBP) 155.3±18.6 mmHg. Mean OSBP reductions after RDN in this higher risk population ranged from −13.1 mmHg at 3 months to −17.5 mmHg at 24 months and −18.9 mmHg at 36 months, and mean ASBP reductions ranged from −7.8 mmHg at 3 months to −9.8 mmHg at 24 months and −9.3 mmHg at 36 months (Figure). Conclusions: Higher risk patients in GSR had sustained office and ambulatory systolic BP reductions out to 3 years after catheter-based radiofrequency RDN. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic